Let love be your guide [compact disc] - Zanes, Dan; Zanes, Claudia (Smithsonian Folkways, 2021)
The first duo album by internationally renowned family musicians Dan and Claudia Zanes is a collection of songs to spark intergenerational conversations about anti-racism, racial justice, and the joys of community. Conceived during the 2020 Black Lives Matter uprisings and coronavirus pandemic, the songs describe the new terms of togetherness, how we understand it, how we build it, and how we strive for more.